Anesthetic complications in a rehabilitation hospital: is the incidence related to the pre-anesthetic visit? - Schwartzman,Ulises Prieto y (2014)
Introduction:Approximately 234 million surgeries are done annually worldwide. There is a growing concern for the safety of the anesthetic act, and the pre-anesthetic consultation emerges as an important and widely recommended activity, used as a preventive measure for the emergence of a complication.Objectives:To describe the complications related to anesthesia, to identify the factors that contribute to its appearance and to reflect on ways to improve clinical practice.Methods:700 patients, 175 cases and 525 controls, were evaluated over a period of 21 months. The data obtained through the pre-anesthetic consultation were evaluated descriptively and then tested with conditional univariate and multivariate logistic regression analysis.Results:175 cases of anesthesia-related complications (2.74%) out of 6365 anesthetic acts were evaluated. Hypotension was the most common complication (40 patients, 22.8%), followed by vomiting (24 patients, 13.7%) and arrhythmia (24 patients, 13.7%). Among the complications, 55% were due to patient conditions, 26% accidental, 10% predictable and 9% iatrogenic. The complications were classified as mild in 106 (61%), moderate in 63 (36%) and severe in six (3%) patients.Conclusion:Patients with more impaired physical status (American Society of Anaesthesiology 3 and 4), with airway disease, tumor or parenchymal disease, diabetes or disorder of lipid metabolism, thyroid disease, former smokers and very prolonged anesthetic acts present a higher risk of anesthesia-related complications. Therefore, they should be actively investigated in the pre-anesthetic evaluation consultation.